Bioethics for the success of climate action - Núñez García, Patricia Jennifer (2022)
Climate change is the world’s most pressing challenge that threatens all life on planet, and caused primarily by human activities that emit exorbitant amounts of carbon dioxide and other greenhouse gases into the atmosphere. This threat multiplier impacts natural and human health, infrastructure and systems. Climate action via mitigation and adaptation is possible, and climate resilient development is within human reach. However, the national and international commitments, and the available solutions to keep global temperatures from rising above 1.5°C, as agreed in the Paris Accord during COP21, have been insufficient in their ambition and execution. Global bioethics for its respect for all life, for its inclusive nature and for recognizing the human being as a responsible administrator of the biosphere, is necessary to promote and achieve effective and fair climate action. This article seeks to encourage the integration of global bioethics in climate resilient development’s planning and implementation.